The influence of the media on government decisions: Evidence from IPOs in China - Li, Yuanpeng; Shi, Haina; Zhou, Yi (Journal of Corporate Finance, 2021)
In contrast to most developed countries that use registration systems, China has implemented an approval system for initial public offering (IPO) applications. As this IPO approval system involves more than a compliance test, the process allows regulators to exercise a large degree of discretion, which provides an opportunity to observe regulators' decision making in capital markets. We examine the outcomes of firms' IPO applications from 2008 to 2014 and find evidence that the media influence regulators' decisions on IPO applications. Specifically, firms that experience negative news coverage are more likely to have their IPO applications rejected. Negative news influences government decisions via both information and monitoring roles. The political connections of a firm can alleviate an adverse outcome from negative news. Moreover, negative news predicts a higher probability of committing fraud as well as lower earnings persistence in the post-IPO period. The evidence from the post-IPO period suggests that the media help improve the efficiency of regulators' decision making. Our results are robust to controlling for endogeneity issues and to adopting alternative measures of news negativity and an alternative sample.